Pemetaan Potensi Desa Tempos Berdasarkan Kondisi Lingkungan Dan Penduduk - Dearto, Ricko; Salsabillah Nunaya JN, Della; Sukma Wardani, Budi; Pratiwi, Armi; Jaaryya, Ainun; Anissa, Ayang; Nurjahratun; Aliana, Lalis; Rafiandy Rizki Asgar, M.; Caesar Rakhmadi, Fakhmi; Hartono, Budi; Ayu Oka Suwati Sideman, Ida (CV. Multi Kreasi Media, 2024)
The development of a region's potential should be guided by mapping the region's potential, so that regional development becomes focused and sustainable. The three components that are considered are environemntal conditions, social conditions of society and economic conditions. Based on this, Tempos village, which is located in West Lombok, has the potential for development towards agrotourism, because the physical condition of the road is formed following the contour of the hilly area, the dominant area functions as agricultural land, the majority of the population is of working age with gender conditions close to equal but the level of education is still low. need training in the future. The community service method used is the Participatory Action Research (PAR) method, where the community is involved from data collection to the formulation of results so that the continuity of the program without assistance will still run well.